Juridical Disparity in Interfaith Inheritance Law: A Comparative Study Between Islamic Law and Positive Law in Indonesia - Pratama Herry Herlambang; Fenny Wulandari (UIN Siber Syekh Nurjati Cirebon, 2025)
The plurality of religions in Indonesia presents significant challenges to the multidimensional implementation of the existing inheritance law. A particularly complex issue arises when heirs hold differing religious beliefs, which may occur due to interfaith marriages among their parents or individual conversions by the heirs themselves. This divergence in faith introduces a dualism of norms, as it contrasts the exclusive normative provisions of Islamic law with the inclusive approach espoused by Indonesian positive law, which seeks to promote substantive justice. This current research aims to investigate juridical disparities within interfaith inheritance law through a normative and comparative juridical approach. The findings suggest that the absence of an integrated legal framework leads to legal uncertainty, creating interpretative gaps that adversely affect individual civil rights. Consequently, this research advocates for the reformulation of national inheritance law arrangements and policies, emphasizing a foundation of sustainable and equitable legal pluralism.